2016
DOI: 10.14202/vetworld.2016.269-275
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological studies of broiler chicken fed diets supplemented with either raw or enzyme treated dandelion leaves and fenugreek seeds

Abstract: Aim:Herbal plants and their derived products are extensively used particularly in many Asian, African, and other countries of the world as they are considered as ideal feed additives because of their non-residual effect and ability to influence the ecosystem of gastrointestinal microbiota in a positive way. Further, the enzymatic treatment of these herbs helps in their efficient utilization by the host. Dandelion leaves and fenugreek seeds have been reported to have positive effect in terms of improving the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
4
13
0
1
Order By: Relevance
“…The microscopic characteristics of the hepatic tissues showed positive impacts on the histomorphologies of the livers, as seen in Figure 1b-d compared to Figure 1a (control group). The histomorphological changes in the present study were comparable to the previous study by Quereshi et al [80], in which the hepatoprotective effects of fenugreek seeds and dandelion leaves in broiler chickens resulted in normal architecture of the hepatic parenchyma. Additionally, the hepatoprotective effects of these phytobiotics were suggested to be due to the presence of flavonoids in dandelion leaves and fenugreek seeds.…”
Section: Histomorphological Analysis Of the Liversupporting
confidence: 91%
“…The microscopic characteristics of the hepatic tissues showed positive impacts on the histomorphologies of the livers, as seen in Figure 1b-d compared to Figure 1a (control group). The histomorphological changes in the present study were comparable to the previous study by Quereshi et al [80], in which the hepatoprotective effects of fenugreek seeds and dandelion leaves in broiler chickens resulted in normal architecture of the hepatic parenchyma. Additionally, the hepatoprotective effects of these phytobiotics were suggested to be due to the presence of flavonoids in dandelion leaves and fenugreek seeds.…”
Section: Histomorphological Analysis Of the Liversupporting
confidence: 91%
“…Mint also contains polyphenolic compounds and hence could possess strong antioxidant properties (Dorman et al, 2003). Further, the supplementation of enzyme in poultry diets has been reported to improve the performance (Yousuf et al, 2012) by degrading non-starchy polysaccharides and improving their digestion; having beneficial effect on gut morphology and thus improving absorption of nutrients (Tufarelli et al, 2007;Yousuf et al, 2011;Qureshi et al, 2016a). In view of such beneficial effects of mint and enzyme, a study was conducted to evaluate the efficiency of mint leaves, with or without enzyme supplementation on blood biochemistry, carcass characteristics and sensory attributes of broiler chicken.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Moreover, CD and the VH: CD ratio are especially important indicators of the cellular turnover at the villous surface. It was previously reported that longer villi and greater villous surface area suggest an enhanced nutrient absorption capability [ 113 - 115 ]. If the CD is deeper, this might indicate a rapid metabolism to maintain the intestinal villi renewal [ 113 , 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that longer villi and greater villous surface area suggest an enhanced nutrient absorption capability [ 113 - 115 ]. If the CD is deeper, this might indicate a rapid metabolism to maintain the intestinal villi renewal [ 113 , 115 ]. Any shortening in the VH or CD could result in a decreased nutrients absorption capability of the intestine [ 114 , 116 ].…”
Section: Discussionmentioning
confidence: 99%